Diabetes mellitus in a Malaysian teaching hospital: prevalence of diabetes mellitus and frequency of testing for hypercholesterolaemia, proteinuria and HBA1c - Ismail, I.S.; Ooi, C.G.; Haizee, H.N.; Kando, D.V.; Lua, G.W.; Phillip, H.; Chan, S.P.; Rokiah, P.; Zaini, A.; Hew, F.L. (2002)
We examined the prevalence of diabetes among inpatients in our hospital, the relationship of the diagnoses on admission to diabetes, and the frequency of testing for HBA1c as a marker of long-term glycaemic control, proteinuria, and hypercholesterolaemia. In addition, patients with raised laboratory plasma glucose without a known history of diabetes mellitus, were studied to see if there had been further evaluation. The overall prevalence of diabetes in our hospital was 25.3% with the highest prevalence found (37.8%) on medical wards, 10.5% of admissions were due directly to diabetes and a further 58.9% of patients were admitted with illnesses which were significantly related to diabetes. Overall testing rates for HBA1c, protenuria and hypercholesterolaemia were less than ideal (51.6, 73.4 and 45.5% respectively). Less than 50% of patients without previuosly diagnosed diabetes but with high plasma glucose values had further evaluation for diabetes. In conclusion, this study has detected a high overall prevalence of diabetes among inpatients in an urban Malaysian hospital. Rates of testing for HBA1c, proteinuria and hypercholesterolaemia, are dissapointingly low, as is further evaluation of patients without known diabetes, but with elevated glucose values. More effective measures to improve the delivery of inpatient diabetes care are needed.